The authority of the provincial superior as major superior about the structures of the province and the members - Stokłosa, Marek (Prawo Kanoniczne, 2021)
The Code of Canon Law of 1983, after talking on the concept of the authority of superiors in general, goes on to deal, in can. 620, of a category of superiors who in the life of the institute has a particular importance, because they govern the entire institute or a part of it, often called a province, or a part of that province equated, or a house "sui iuris". The notion of "major superiors" includes the figure of the provincial superior. The authority of the provincial superior as major superior, founded on communal authority, extends over the entire religious province entrusted to him and over all its houses, including their activities, and over the individual members who are part of it. This authority is exercised, in accordance with universal canon law and that proper to each institute, with respect for the specific competences of the other superiors, that is, the supreme moderator and the local superiors. The task of proper law, while respecting the communal canon law, is to define the functions proper to each degree of superiors, in order to avoid undue interference and conflicts of authority. In the article the specific faculties of the provincial superior collective to all the major superiors of any religious institute attributed by canon law regarding the structures of the province and its members were indicated. It is obvious that it is difficult to compile exhaustively the list of all the faculties of the provincial superior as major superior. Surely the daily life of individual religious, as well as of the communities in which they live and of the various activities of the province, present many cases that require the intervention of the provincial superior who is often not contemplated either by the norms of universal canon law or proper law, or by the customs of the province or institute. These cases depend on the size of the province in its various factors, beginning with the resources of personnel and materials, as well as the various activities proper to the Province or entrusted to it by the competent ecclesiastical authority. The authority of the provincial superior as major superior in some cases is conditioned, according to the canon law, by a particular intervention of his own council, or even limited by the fact that he must submit certain cases to the authority of the superior general: cases for which the decision, on the basis of universal canon law or proper law, is reserved to the supreme moderator, with a certain intervention, or not, of his council. In the field of the structures and activities of religious, the authority of the provincial superior is limited by only one faculty reserved for the competence of the superior general, that is, the canonical suppression of the legitimately erected house (can. 616 § 1). Any other limitations of the authority of the provincial superior depend on the proper law of the institute, reserving certain faculties to the supreme moderator.